Evaluation of new laser spectrometer techniques for in-situ carbon monoxide measurements - C. Zellweger; M. Steinbacher; B. Buchmann (Atmospheric Measurement Techniques, 2012)
Long-term time series of the atmospheric composition are essential for environmental research and thus require compatible, multi-decadal monitoring activities. The current data quality objectives of the World Meteorological Organization (WMO) for carbon monoxide (CO) in the atmosphere are very challenging to meet with the measurement techniques that have been used until recently. During the past few years, new spectroscopic techniques came to market with promising properties for trace gas analytics. The current study compares three instruments that have recently become commercially available (since 2011) with the best currently available technique (Vacuum UV Fluorescence) and provides a link to previous comparison studies. The instruments were investigated for their performance regarding repeatability, reproducibility, drift, temperature dependence, water vapour interference and linearity. Finally, all instruments were examined during a short measurement campaign to assess their applicability for long-term field measurements. It could be shown that the new techniques perform considerably better compared to previous techniques, although some issues, such as temperature influence and cross sensitivities, need further attention.